(untitled) (Journal of Academic Research, 2025)
Background: Persistent primary hyperparathyroidism (PHPT) after surgery is often due to missed ectopic or supernumerary glands. Reoperation is challenging and requires precise imaging, anatomical understanding, and surgical expertise. Methods: A 34-year-old woman with classic PHPT symptoms and biochemical evidence (Ca: 12.75 mg/dL, PTH: 891 pg/mL) underwent two failed parathyroidectomies. Imaging was inconclusive; histology showed nodular hyperplasia in the first and absence of parathyroid tissue in the second. A third surgery, guided by high-resolution ultrasound and intraoperative endoscopy, located an ectopic retroesophageal adenoma, which was excised. Results: Immediate postoperative laboratory confirmed cure (Ca: 7.2 mg/dL, PTH: <1.2). The patient developed transient hungry bone syndrome. No complications were noted. Conclusion: Persistent PHPT requires high suspicion for ectopic or supernumerary glands. Third-time parathyroidectomy, when planned with expert imaging and surgical collaboration, can be safe and curative.